Penerapan Terapi Bermain Puzzle Pada Anak Pra Sekolah Dengan Kejang Demam Untuk Mengurangi Kecemasan - Yusnita -; Andri Yulianto; Tiara -; Dika Arlita (Jurnal Kesehatan Panca Bhakti Lampung (JKPBL), 2020)
In Indonesia, the incidence of fever convulsions in the amount of percentage that is well balanced with other countries is reaching 3-4%. Fever seizure in 2016 as many as 167 children and in 2017 as much as 155 ana (record Medical Hospital RSUD Dr. Hi. Abdul Moeloek, 2017). Sick children will experience stress and anxiety. The study aims to determine the application of the pre-school puzzle play therapy to reduce the anxiety of fevering fever in the natural spaces of Dr. Hi District General Hospital. Abdul Moeloek Provnsi Lampung Year 2019.The design used in the study was a case study. The participants used are 2 patients aged 1-5 years old with a diagnosis of fever seizures. The Instrument used in this study is the HRS-A-scale anxiety observation sheet and Puzzle image consisting of 6 parts. The results of the study, on the 3rd day of both patients experienced a decrease in anxiety levels, in patients 1 before being given the therapy play an anxiety scale 8 and patient 2 scale anxiety 7. Both patients experienced the same decline of 4 on the third day. It is expected that nurses can give play therapy especially playing puzzles on pre school children to reduce anxiety.